Sustainable Fashion and Everyday Practices (ModaPalavra e-periódico, 2018)
This is an interview with Prof. Ana Beatriz Simon Factum, about sustainability and social practices to enable a more responsible world with the environment. She participates in the research group Design, Sustainability and Social Responsibility of the University of the State of Bahia, and talks about her academic career and her insertion in the universe of sustainable fashion. The interviewee gives her opinion about the fashion movement in the search for a more sustainable way and the need to identify joint actions in favor of a more conscious world.
Keywords: sustainability; fashion; social practices